An Observational Study for the Assessment of Adverse Drug Reactions of Platinum Based Chemotherapy in Cancer Patients at Sms Hospital, Jaipur - Dr. Ashish Sharma; Dr. Sushil Sharma; Dr. Charu Jain (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Platinum analogues—cisplatin, carboplatin and oxaliplatin—are the cornerstone of many solid tumour regimens but are limited by a broad spectrum of adverse drug reactions (ADRs). Robust Indian pharmacovigilance data in real world oncology settings remain scarce. Methods: We conducted a hospital based, prospective, descriptive observational study (April 2023 – March 2024) among 100 consecutive adult and paediatric cancer patients who developed at least one ADR while receiving a platinum agent in the Department of Medical Oncology, SMS Hospital, Jaipur. ADRs were characterised and uploaded to VigiFlow. Causality (WHO UMC), severity (modified Hartwig–Siegel) and preventability (modified Schumock–Thornton) were assessed; outcomes and seriousness were recorded. Results: A total of 467 ADRs were documented (median 4, IQR 3–6 per patient). Central nervous system manifestations predominated (35.8 %), followed by haematological (26.6 %) and gastrointestinal (19.5 %) systems. Nausea (14.8 %), vomiting (10.1 %), anaemia (13.1 %) and alopecia (6.9 %) were most frequent. Carboplatin was the most commonly used agent (57 % of patients) yet showed no statistically significant difference in ADR profile versus cisplatin or oxaliplatin (p > 0.3 for all comparisons). WHO UMC categorised 96.2 % of ADRs as possible and 3.8 % as probable. Severity was predominantly moderate (60.8 %); no life threatening reactions were observed. Almost half of all ADRs (49.0 %) were definitely preventable. All events were either recovering (68 %) or recovered (32 %) at last contact; none were fatal. Conclusion: Platinum chemotherapy produces a predictable but largely preventable burden of predominantly moderate ADRs in Indian oncology practice. Systematic monitoring, timely supportive care and proactive patient counselling can mitigate toxicity and optimise treatment continuity.